Hotspots of vascular plant endemism in a global biodiversity hotspot in Southwest Asia suffer from significant conservation gaps. (September 2019) - Noroozi, Jalil; Naqinezhad, Alireza; Talebi, Amir; Doostmohammadi, Moslem; Plutzar, Christoph; Rumpf, Sabine B.; Asgarpour, Zahra; Schneeweiss, Gerald M.
Abstract: Biodiversity loss due to human activities has dramatically increased in the last decades, and attempts to protect threatened species should be accelerated. An important contribution towards this goal is to identify areas rich in biodiversity and endemism, where conservation will be most efficacious. Here, we follow this strategy for Iran, which includes large parts of the Irano-Anatolian global biodiversity hotspot, to assess the extent of conservation gaps. Based on nearly 25, 000 records from about 2600 (sub-)endemic vascular plant species, we determine centres of endemism using three well-established biodiversity indices (endemic richness, range-restricted endemic richness, range-rarity richness). Considering only areas (grid cells) where these indices were highest (10%/5%-based quantiles), a total of 74/39 grid cells are identified as Hotspots (centres of endemism supported by at least one index), and 30/18 grid cells are identified as Priority Hotspots (centres of endemism supported by all three indices). All hotspots are inside the Irano-Anatolian biodiversity hotspot and inside previously identified areas of endemism. Although the 10%/5%-quantile-based Priority Hotspots cover only 5%/3% of the Iranian surface area, they contain 59%/47% of the endemic plant species of Iran. Yet, Priority Conservation Gaps (Priority Hotspots not covered by nature reserves) amount to 47%/50% compared to 59%/54% for Conservation Gaps (Hotspots not covered by nature reserves). Evidently, there is a major discrepancy in the Irano-Anatolian biodiversity hotspot between an area being a centre of unique plant diversity and the protection status of this area. Considering the growing pressure on these areas due to, for instance, global climate change or increasing anthropogenic land use, establishment of new nature reserves in both the Conservation Gaps and especially the Priority Conservation Gaps as well as the increased efficacy of the already established nature reserves in the identified hotspots is necessary.